Looks and images: video and photo therapy. - Rossi, Oliviero (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2014)
The art therapytechniques are increasinglyrenewed by the use of new instrumentsas new media (video and photo).Working with imagesis a powerful way to increase the client’sawareness in psychotherapy, because the perceptiveactcouldbringthe therapist to construct with the client the story of his life. The familypictures or personal snapshots are precious and important to stimulate the creative process, the use of metaphors and the contact with emotions. In thisregard, wewillexamine the concepts of personal growth, helping relationship and thesis of existence in the frame of the Gestaltpsychotherapy model. The work isexplaineddeeply, after a theoricalintroduction, takinginspiration from asession of psychotherapy in which the patientworkswith personal photographs.